New nano-structured and interactive supported composite electrocatalysts for hydrogen evolution with partially replaced platinum loading - Perica Paunovic, Ivan Radev, Aleksandar T. Dimitrov, Orce Popovski, Elefteria Lefterova, Evelina Slavcheva, Svetomir Hadzi Jordanov (Elsevier, 2009)
This work is concerned with preparation and characterization of nano-structured composite electrocatalytic material for hydrogen evolution based on CoPt hyper d-metallic phase and anatase (TiO2) hypo d-phase, both deposited on multiwalled carbon nanotubes (MWCNTs) as a carbon substrate. The main goal is partially or completely to replace Pt as the electrocatalytic material. Four electrocatalytic systems were prepared with common composition 10% Me þ 18% TiO2 þ MWCNTs, where Me ¼ Co, CoPt (4:1, wt. ratio), CoPt (1:1, wt. ratio) and Pt. The structural changes and their influence on electrocatalytic activity were studied by means of XRD, TEM, SEM and FTIR. The electrocatalytic activity was assessed in aqueous alkaline and polymer acidic electrolytes by means of steady-state galvanostatic method. It was found that Co strongly affects the platinum particle size. The addition of Co reduces platinum particle’s size from 11 nm (in pure Pt metallic system) to 4 nm (in both systems 4:1 and 1:1), i.e. almost by 3 times. The corresponding increase of the surface area and the number of the active catalytic centres improves the efficiency, despite the fact that the amount of used platinum was decreased up to 5 times. The catalyst based on CoPt (1:1) performed the best, while the activity of the pure platinum and CoPt (4:1) systems were very close. Generally, the studied electrocatalysts have shown good and stable performances for hydrogen evolution in PEM electrochemical cell. The influence of the hydrogen electrodes under investigation on the water electrolysis efficiency at current density of 0.3 A cm 2 was assessed, using previous data oxygen evolution on IrOx electrode. Related to the performances of commercial Pt (ELAT) electrode, when hydrogen electrodes with the prepared mixed electrocatalysts were used, the water electrolysis efficiency was only 5% lower for CoPt (1:1), nearly 10% lower for CoPt (4:1) and 13% lower in the case of pure Co-based electrocatalyst.